Bilimsel Toplantı Duyuruları - Adli Tıp Uzmanları Derneği ATUD (Adli Tıp Bülteni, 2000)
1 IV. Adli Bilimler Kongresi 10-13 Mayıs 2000, İstanbul İ.Ü. İstanbul Tıp Fakültesi Adli Tıp AD ve Adli Tıp Uzmanlan Derneği (ATUD) İletişim: Dr. Eren Karpuzoğlu, İ.Ü. İstanbul Tıp Fakültesi Adli Tıp AD 34390, Çapa, İstanbul Tel:0-212-6351179 2 Vth International Conference On Pediatric Trauma 17-20 Haziran 2000 Vail, Colorado, ABD Dr. Burton Harris Tel: (719) 365-5888 e-mail: bharris@memhospcs.org 3 International Assoc, for Identification Annual Conference July 23-29, 2000 Embassy Suites, Charleston, WV Contact: Candy Murray 20601 Netherland St. Orlando, FL 32833 (407) 568-7436 conference@theiai.org 4 Death and the Maiden - Murder and Rape Investigation. Summer Meeting of the Forensic Science Society. 7- 9 July 2000. College of Ripon and York, St John, York, North Yorkshire, U.K. 5 The 13th World Congress on Medical Law 6- 10 August, 2000 World Association for Medical Law Helsinki, Finland. contact Stakes/Eva Lindbergh, Siltasaarenkatu 18, P.O. Box 220, FIN-0053, Helsinki, Finland, phone +358 9 3967 2173, FAX +358 9 3967 2030, email: eva.lindberg@stakes.fi 6 5th International Conference in Clinical Forensic Medicine of the World Police Medical Officers. 16-20 August 2000. WPMO 2000, 568-999 Canada Place, Vancouver, BC, Canada, V6C 3E1. 7 16th meeting of the International Association of Forensic Sciences. 1-7 September 2000 Convention Center Le Corum, Montpellier, France. Contact: Societe Internationale de Congres et Services, 337, rue de la Combe Caude, 34090 Montpellier, France. Tel +33 (0)4 67 63 53 40. Fax +33 (0)4 67 41 94 27. E-mail algcsi@mnet.fr 8 Crime Scene Technology Workshop 3 Advanced Techniques September 25-29, 2000 Portland, OR Contact: Registrar Northwestern University, Traffic Institute 405 Church St. Evanston, IL 60201 (800) 323-4011 9 Joint Meeting with the Forensic Science Service: - Crimes of the Millennium. 3- 5 November 2000. Stakis Hotel, Bromsgrove, Birmingham. Convener; Mike Loveland. Details from Forensic Science Society Office. Tel: 01423 506068 10 Investigative Photography Workshop I Comprehensive Photographic Techniques December 4-8, 2000 Evanston, IL Contact: Registrar Northwestern University, Traffic Institute 405 Church St. Evanston, IL 60201 (800) 323-4011